MRSA Incidence and Antibiotic Trends in Urban Hand Infections: A 10-Year Longitudinal Study. (July 2019) - Kistler, Justin M.; Thoder, Joseph J.; Ilyas, Asif M.
Background: Methicillin-resistant Staphylococcus aureus (MRSA) is the most reported pathogen in hand infections at urban medical centers throughout the country. Antibiotic sensitivity trends are not well known. The purposes of this study were to examine and determine the drug resistance trends for MRSA infections of the hand and to provide recommendations for empiric antibiotic treatment based on sensitivity profiles.Methods: A 10-year longitudinal, retrospective chart review was performed on all culture-positive hand infections encountered at a single urban medical center from 2005 to 2014. The proportions of all organisms were calculated for each year and collectively. MRSA infections were additionally subanalyzed for antibiotic sensitivity.Results: A total of 815 culture-positive hand infections were identified. Overall, MRSA grew on culture in 46% of cases. A trend toward decreasing annual MRSA incidence was noted over the 10-year study period. There was a steady increase in polymicrobial infections during the same time. Resistance to clindamycin increased steadily during the 10-year study, starting at 4% in 2008 but growing to 31% by 2014. Similarly, levofloxacin resistance consistently increased throughout the study, reaching its peak at 56% in 2014.Conclusions: The annual incidence of MRSA in hand infections has declined overall but remains the most common pathogen. There has been an alternative increase in the number of polymicrobial infections. MRSA resistance to clindamycin and levofloxacin consistently increased during the study period. Empiric antibiotic therapy for hand infections should not only avoid penicillin and other beta-lactams but should also consider avoiding clindamycin and levofloxacin for empiric treatment.